Competitive Counterion Binding Regulates the Aggregation Onset of Vimentin Intermediate Filaments. Issue 8 (23rd February 2015) - Dammann, Christian; Herrmann, Harald; Köster, Sarah
Abstract: Aggregation is a commonly observed phenomenon when mixing charged biopolymers and counterions. However, it remains a challenge to find a general description for the involved mechanisms. Here, we investigate vimentin intermediate filaments, which are overall highly negatively charged, as a prime example of such biological polyelectrolytes. We experimentally determine the onset cation concentration for aggregation, and set it in relation to the calculated relative cation concentrations in the vicinity of the filament surface. Our analysis shows that to achieve aggregation, about 50 % of the monovalent cations originally present have to be replaced by di‐ or multivalent cations. We are thus able to predict the bulk cation concentration, which mediates aggregation of highly negatively charged vimentin filaments. Abstract :